Assessment of Student Nurses' Self-Efficacy and Performance by using Simulation-Based Learning (SBL) - Razia, .; Shahzadi, Naila; Pervaiz, Ailka; Sumaira, .; Amir, Zunira; Tasneem, Syeda Sidra; Jabeen, Rubina (Biological and Clinical Sciences Research Journal, 2025)
Simulation-Based Learning (SBL) is increasingly recognized as a transformative teaching strategy in nursing education, bridging the gap between theoretical instruction and practical application. By fostering self-efficacy, SBL has the potential to enhance clinical competence, reduce errors, and better prepare nursing students for the real-world challenges of healthcare. Objective: To assess the effectiveness of simulation-based learning in enhancing self-efficacy and clinical performance among post-RN nursing students in Pakistan. Methods: A quantitative, descriptive, cross-sectional study was conducted among 110 post-RN BSN students at Superior College of Nursing, Lahore. Participants were assigned to either a simulation-based training group (the intervention) or a traditional clinical rotation group (the control). Data were collected in July 2024 using a structured, pre-validated questionnaire incorporating the Self-Efficacy Scale (SES) and an Objective Structured Clinical Examination (OSCE). Statistical analysis was performed using SPSS version 23. Descriptive statistics summarized demographics, while paired t-tests and ANOVA evaluated differences between groups. Results: Students in the simulation group showed a significant improvement in self-efficacy scores compared to the control group (pre-test mean 62.5 vs. post-test mean 79.3; p < 0.01). OSCE performance outcomes revealed a 28% increase in procedural accuracy (88% vs. 60%) and a 25% reduction in clinical errors (1.5 vs. 4.0 per 10 cases) in the simulation group relative to controls (p < 0.01). Thematic analysis of reflective journals identified three major themes: increased confidence, enhanced preparedness, and reduced anxiety during clinical practice. Conclusion: Simulation-based learning significantly improves self-efficacy, procedural accuracy, and clinical decision-making while reducing errors and anxiety among nursing students. Integrating SBL into nursing curricula is strongly recommended to foster confident, competent, and practice-ready graduates capable of delivering safe and high-quality patient care.